REPRESENTASI PERLAWANAN TERHADAP OLIGARKI DALAM FILM “GUNDALA” - Adhi Wiryawan, Yudho; Bayu Widagdo, Muhammad; Rahardjo, Turnomo (Interaksi Online, 2024)
Superheroes are a type of popular culture are related with Great Depression in Unaited State. Superheroes represent people's hopes and dreams in solving their problems. Today's superhero movies not only focus on commercial needs but they also bring social issues into their stories. Gundala, a film directed by Joko Anwar which was released in 2019 based on the comic character written by Hasmi. Joko Anwar made adjustments in this movie and included current social issues as a form of freedom of speech that could not be done openly at the time the Gundala comic was made. Resistance as a form of social movement is carried out by society to make social changes that affect their lives. This research aims to determine resistance of oligarchy as represented in the Gundala (2019) movie and the forms of resistance carried out by society against oligarchy. Using deprivation theory as a theory of social movements in order to create social change. This qualitative research is using John Fiske's semiotic analysis method to analyse scenes that represent resistance of oligarchy in Gundala. The results of this research found that oligarchy is described as great strength and power that is difficult to fight alone. Resistance was carried out by people from various social classes as an illustration of oligarchy power that affected all levels of society. Resistance is dominated by group resistance because of the difference in power between society and oligarchy. People who resist individually tend to show their resistance behind their backs because direct individual resistance is considered to be dangerous to them. Therefore, people group together to fight back in order to have power equal to oligarchy. Gundala represent people’s hope to take the oligarchy down.